2018
DOI: 10.5121/ijmvsc.2018.9101
|View full text |Cite
|
Sign up to set email alerts
|

Critical Factors and Enablers of Food Quality And Safety Compliance Risk Management in the Vietnamese Seafood Supply Chain

Abstract: Recently, along with the emergence of food scandals, food supply chains have to face with ever-increasing pressure from compliance with food quality and safety regulations and standards. This paper aims to explore critical factors of compliance risk in food supply chain with an illustrated case in Vietnamese seafood industry. To this end, this study takes advantage of both primary and secondary data sources through a comprehensive literature research of industrial and scientific papers, combined with expert in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Further, if Q(t) = 0, the optimal discount ratios would degenerate to the result proposed in [6,16,43]; if Q(t) = exp(a − bt), the optimal discount ratios would degenerate to the result proposed in [34]; if Q(t) is far larger than the normal quantity (i.e., it is a supernormal disruption, in which an extreme and sudden disruption occurs), the result calculated would match that shown in [16]. This proves Theorem 2 is correct.…”
Section: A Universal Coordination Strategy For Multi-stage Discountsmentioning
confidence: 83%
“…Further, if Q(t) = 0, the optimal discount ratios would degenerate to the result proposed in [6,16,43]; if Q(t) = exp(a − bt), the optimal discount ratios would degenerate to the result proposed in [34]; if Q(t) is far larger than the normal quantity (i.e., it is a supernormal disruption, in which an extreme and sudden disruption occurs), the result calculated would match that shown in [16]. This proves Theorem 2 is correct.…”
Section: A Universal Coordination Strategy For Multi-stage Discountsmentioning
confidence: 83%
“…In the traditional supply chain, the demand function is divided into two categories: Equation ( 26) describes the first step before the discount is applied; and Equation (27) maps the changes to supply price and demand quantity afterwards (Liu et al, 2020 [10] ; Zhang et al, 2017 [30] ). It is concluded that the common intercept exists in both…”
Section: The Single-stage Discount Approachmentioning
confidence: 99%
“…) exp( ( ) It has been proven that the profit produced in centralized decision-making is greater than or equal to that of decentralized decision-making. Accordingly, the corresponding discount ratios are also more reliable (Tran 2018 [27] ).…”
Section: Optimal Discount Ratios In Multi-stage Discount Strategiesmentioning
confidence: 99%